Annona glabra Flavonoids Act As Antimicrobials by Binding to Pseudomonas aeruginosa Cell Walls - Galvão, Stanley de S. L.; Monteiro, Andrea de S.; Siqueira, Ezequias P.; Bomfim, Maria Rosa Q.; Dias-Souza, Marcus Vinícius; Ferreira, Gabriella F.; Denadai, Angelo Márcio L.; Santos, Áquila R. C.; Lúcia dos Santos, Vera; Souza-Fagundes, Elaine M. de; Fernandes, Elizabeth S.; Monteiro-Neto, Valério (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosa is an important pathogen in opportunistic infections in humans. The increased incidence of antimicrobial-resistant P. aeruginosa isolates has highlighted the need for novel and more potent therapies against this microorganism. Annona glabra is known for presenting different compounds with diverse biological activities, such as anti-tumor and immunomodulatory activities. Although other species of the family display antimicrobial actions, this has not yet been reported for A. glabra. Here, we investigated the antimicrobial activity of the ethyl acetate fraction (EAF) obtained from the leaf hydroalcoholic extract of A. glabra. EAF was bactericidal against different strains of P. aeruginosa. EAF also presented with a time- and concentration-dependent effect on P. aeruginosa viability. Testing of different EAF sub-fractions showed that the sub-fraction 32-33 (SF32-33) was the most effective against P. aeruginosa. Analysis of the chemical constituents of SF32-33 demonstrated a high content of flavonoids. Incubation of this active sub-fraction with P. aeruginosa (ATCC 27983) triggered an endothermic reaction, which was accompanied by an increased electric charge, suggesting a high binding of SF32-33 compounds to bacterial cell walls. Collectively, our results suggest that A. glabra-derived compounds, especially flavonoids, may be useful for treating infections caused by P. aeruginosa.